2023
DOI: 10.3390/ma16020682
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PLLA/MgF2 Coating on Mg Alloy by Ultrasonic Atomization Spraying for Controlling Degradation and Improving Biocompatibility

Abstract: Problems of rapid degradation and poor biocompatibility (endothelialization and hemocompatibility) limit magnesium (Mg) alloy’s further applications in vascular stents. To solve these problems, a novel composite coating was designed on Mg alloy via a two-step method. First, a Mg alloy sample was immersed in hydrofluoric acid. Then, a poly-l-lactic acid (PLLA) coating was made by ultrasonic atomization spraying with 5 and 10 layers (referred to as PLLA(5)-HF-Mg and PLLA(10)-HF-Mg). Characterizations were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The SEM image of the base alloy and the fluoridetreated specimen's cross-section showed the thickness of the MgF2 layer as Figure 6. the coating layer, with a thickness of approximately 14.21 μm, adhered to the Mg-2Al-1Nd alloy substrate well shown in Figure 6, and It was also found that increasing the time of immersing the Alloy in H.F. solution increases the thickness of the layer formed [2,17].…”
Section: Characterization Of Coating and Alloymentioning
confidence: 58%
See 1 more Smart Citation
“…The SEM image of the base alloy and the fluoridetreated specimen's cross-section showed the thickness of the MgF2 layer as Figure 6. the coating layer, with a thickness of approximately 14.21 μm, adhered to the Mg-2Al-1Nd alloy substrate well shown in Figure 6, and It was also found that increasing the time of immersing the Alloy in H.F. solution increases the thickness of the layer formed [2,17].…”
Section: Characterization Of Coating and Alloymentioning
confidence: 58%
“…It should be noted that during fluoride treatment, hydrogen (H2) is produced, resulting in a porosity coating. The fluoride conversion layer is usually thin as well (16)(17)(18) μm; as a result of this, both the anti-corrosion capability and layer of coating tend to be sub-bar [9,38]. Lou et alin 2021 [30] Studied the effect of coating magnesium fluoride on a plate of pure magnesium.…”
Section: Introductionmentioning
confidence: 99%
“…Mg alloy disks were immersed in Eagle's minimal essential medium (EMEM) supplemented with 10% FBS and 100 mg/mL penicillin and streptomycin at 37°C under a 5% CO 2 atmosphere in standard 6‐well culture plates for 4 weeks. A corrosion test was performed using a surface area to immersion medium volume ratio of 1.25 cm 2 /mL according to ISO 10993‐12 18 . The medium was collected every week, and new medium was added to the Mg alloy disks.…”
Section: Methodsmentioning
confidence: 99%
“…A corrosion test was performed using a surface area to immersion medium volume ratio of 1.25 cm 2 /mL according to ISO 10993-12. 18 The medium was collected every week, and new medium was added to the Mg alloy disks. Subsequently, diammonium hydrogen citrate (300 mg/mL, 500 μL) was introduced into the medium to dissolve the insoluble corrosion products of Mg alloy disks via an ultrasound treatment for 5 min.…”
Section: In Vitro Corrosion Testmentioning
confidence: 99%
“…The MgF 2 layer on the surface of magnesium alloys is smooth and compact, but with some micropores. The preparation of PLLA coatings using ultrasonic atomization spraying could well cover these pores and provide a good physical barrier [ 103 ]. The fluoride-treated magnesium alloy stents could remain unchanged in the neutral axis direction after crimping and dilating with a balloon catheter, while the coating appeared brittle and flaky at the deformed radius.…”
Section: Traditional Strategy For the Protection Of Magnesium Alloy S...mentioning
confidence: 99%